The Effect Of Family Support And Education On The Level Of Anxiety Of Pulmonary TB Patients In Community Lung Health Center (BKPM) Purwokerto - Karomah Budijarto, Alifia Putri; Purbowati, Mustika Ratnaningsih; Riyanto, Refni; Basuki, Dyah Retnani (Herb-Medicine Journal: Terbitan Berkala Ilmiah Herbal, Kedokteran dan Kesehatan, 2021)
Pulmonary tuberculosis is a disease with a long duration of treatment and involves wide types of drugs which couldcause various adverse andharmful effects, then further could cause the risk of emotional changes such as anxiety. Therole of family support and education in reducing mortality, the escalating incidence rate of pulmonary TB in CentralJava Province, the unachieved target of successful TB treatment and also high rates of anxiety in TB patient, affirmthe necessity to conduct this research.To determine the effect of family support and education on the anxiety levelsamong pulmonary TB patients in BKPMPurwokerto.The type of this research is a quantitative study using a cross-sectional design. This research was conducted at the Purwokerto Community Lung Health Center with Spearman testas the hypothesis test used in the research.The analysis result shows the influence of family support on anxiety levelsobtained a p value <0.05 meanwhileÂ  the influence of education on anxiety levels acquired a p value> 0.05.Familysupport could affect significantly while education could not significantly affect the anxiety levels in pulmonary TBpatients at BKPM Purwokerto